THE IMPACT OF NATIONAL GINGER PRODUCTION, IDR/BDT EXCHANGE RATE, PARTNER COUNTRY GDP, AND INDONESIA’S INFLATION ON INDONESIA’S GINGER EXPORT VALUE TO BANGLADESH (2014–2024) - Azka Septianto; Tria Apriliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of national ginger production, the IDR/BDT exchange rate, Bangladesh’s Gross Domestic Product (GDP), and Indonesia’s inflation on the value of Indonesian ginger exports to Bangladesh during the period 2014–2024. The research employs a quantitative approach using time series secondary data obtained from Statistics Indonesia, Bank Indonesia, the World Bank, and other official sources. The independent variables consist of national ginger production, the IDR/BDT exchange rate, Bangladesh’s GDP, and Indonesia’s inflation, while the dependent variable is the value of ginger exports. Data were analyzed using multiple linear regression with the assistance of EViews 13 software. The results indicate that, partially, national ginger production does not have a significant effect on the value of Indonesian ginger exports to Bangladesh. The IDR/BDT exchange rate has a significant effect on export value, indicating that exchange rate movements play an important role in determining export competitiveness. Furthermore, Bangladesh’s GDP has a negative and significant effect on Indonesian ginger export value, suggesting that economic growth in the partner country does not necessarily lead to increased imports of Indonesian ginger. Meanwhile, Indonesia’s inflation does not show a significant effect on export value. Simultaneously, all independent variables have a significant effect on the value of Indonesian ginger exports to Bangladesh